The role of artificial intelligence technologies in protecting the environment and enhancing its sustainability - Al Maagbeh, Moh'd Mofadi Faleh; Altarawneh, Mohammad Meeush; E`layan, Mahasen Khalaf; Al Dalaien, Ahmad A; Alayaydeh, Hamza Ali Suleiman; Al-Tarawneh, Doha Ibrahim; Baniamer, Asem; Alhendi, Noor; Altarawneh, Shadi Meeush D’yab; Alhusban, Odeh Abdul Kareem Khalil (Research Journal in Advanced Humanities, 2026)
This study explores the role of artificial intelligence (AI) technologies in protecting the environment and enhancing its sustainability. AI technologies can perform specific environmental tasks to improve, preserve, and enhance the sustainability of environmental elements, and to provide effective environmental solutions. Hence, this study aims to reveal the essence of AI by explaining its concept, importance, and advantages. It also aims to explore its applications in environmental protection, as well as the ethics, risks, and balances associated with its use in the environment. To address this topic systematically, the study adopted a descriptive and analytical approach, because it is suitable for facilitating the process of examining the subject, and it leads to accurate scientific results that enhance understanding of the role of AI systems in protecting and enhancing environmental sustainability. The study concluded that AI is an effective tool for preserving the environment and supporting sustainability efforts by improving natural resource management, reducing emissions, and monitoring climate change with high accuracy. Finally, the study recommends strengthening environmental legislation and policies that regulate the use of AI technologies to ensure the protection of the environment and natural resources. It also recommends developing green, low-energy algorithms to reduce the carbon footprint of data centers and smart systems, in addition to integrating environmental ethics standards into the design and application of AI systems in order to ensure respect for privacy and social justice.